In Silico Study of Compounds Bioactive Guava (Psidium guajava) as Antidiarrheal Assisted Liquid Chromatography-Mass Spectroscopy - Cendekiawan, Khrisna Agung; Kintoko, Kintoko; Yuliani, Sapto; Anggraeni, Linda Suci; Ningrum, Lailatul Fitria; Hasana, Siti Nur; Wardhani, Firdha Aprillia (Program Studi Farmasi Universitas Mandala Waluya, 2025)
Guava leaves seeds (Psidium guajava) are known contain various compound potential bioactives? as antidiarrheal, such as quercetin and tannins, which work with method hinder intestinal contractions and disrupts permeability membrane cell bacteria. Research This aim for explore potential antidiarrheal from compound in leaf guava seed through identification compound using LC-MS and simulation molecular docking to six human protein target receptors, namely Cytochrome P450 1A1, Ephrin Type-B Receptor 4, Multidrug Resistance Protein 1, Dihydrofolate Reductase, Extracellular Calcium-Sensing Receptor, and Rap Guanine Nucleotide Exchange Factor 4. Extraction done with method maceration use solvent methanol, then compound analyzed using Liquid Chromatography–Mass Spectrometry (LC-MS). A total of eleven compound main chosen foranalyzed in silico using device soft AutoDockTools, PyRx, and Discovery Studio. Validation was performed through redocking of native ligands with RMSD value ? 2 Å. The results show some ligands such as Kaempferol, Cathecin, and Quercetin own affinity strong bond, with? Kaempferol show lowest binding energy of -9.72 kcal /mol against BHF receptor. Drug-likeness test based on Lipinski's rule also shows that part big compound fullfil criteria compound drug analysis? interaction amino acids show existence bond hydrogen and hydrophobic support? stability bond. This result show that compound leaf guava seeds, especially Kaempferol and Cathecin, potentially as candidate agent antidiarrheal natural. Further studies in vitro and in vivo are recommended for support findings.